GUARANTEE PRODUCT PORTFOLIO: PERFORMANCE AND OPTIMAL PORTFOLIO ANALYSIS - Santosa Santosa; Noer Azam Achsani; Hendro Sasongko (Universitas Pakuan, 2020)
This study aims to analyze the performance of guarantee products and optimize guarantee portfolio at PT Penjaminan ABC. The method used in forming the optimal guarantee portfolio is the Markowitz method and the single index model. The results of the formation of optimal portfolios based on the Markowitz method show that there are five eligible guarantee products included in the optimal guarantee portfolio, namely construction financing, counter bank, general financing, micro financing, and multi-use financing. While custom bond, surety bonds, and other guarantees are not included in the optimal portfolio. In contrast to the Markowitz method, based on the single index model, all guarantee products are not eligible to be included in the optimal guarantee portfolio. Managerial implications of the optimal guarantee product portfolio is an increase in guarantee returns which will further increase company profits and increase company equity. An increase in company equity will reduce the gearing ratio in order to comply with regulations, because the gearing ratio is calculated by dividing the outstanding guarantee volume by the total equity.